Secret habits : Catholic literacy education for women in the early nineteenth century - Mattingly, Carol, 1945- (Carbondale : Southern Illinois University Press, 2016)
"Literacy historians have credited the Protestant mandate to read scripture, as well as Protestant schools, for advances in American literacy. This belief, however, has overshadowed other important efforts and led to an incomplete understanding of our literacy history. In Secret Habits: Catholic Literacy Education for Women in the Early Nineteenth Century, Carol Mattingly restores the work of Catholic nuns and sisters to its rightful place in literacy studies. Mattingly shows that despite widespread fears and opposition, including attacks by vaunted northeastern Protestant pioneers of literacy, Catholic women nonetheless became important educators of women in many areas of America. They founded convents, convent academies, and schools; developed their own curricula and pedagogies; and persisted in their efforts in the face of significant prejudices. The convents faced sharp opposition from Protestant educators, who often played on anti-Catholic fears to gain support for their own schools. Using a performative rhetoric of good works that emphasized their civic involvement, Catholic women were able to educate large numbers of women and expand opportunities for literacy instruction. A needed corrective to studies that have focused solely on efforts by Protestant educators, Mattingly's work offers new insights into early nineteenth-century women's literacy, demonstrating that efforts at literacy education were more religiously and geographically diverse than previously recognized. Secret Habits chronicles the adversity Catholic nuns and sisters faced as they worked to provide literacy instruction to women in early America."--
""Secret Habits" contributes to our understanding of women's literacy in the nineteenth century by critically examining literacy studies' acceptance of the Protestant literacy myth, the curriculum and pedagogy of Catholic schools, and the ways in which Catholic nuns and sisters worked to alleviate biases toward them and their religion"--
Machine generated contents note: Table of Contents -- Preface -- Acknowledgements -- Chronology -- Introduction: Beyond the Protestant Literacy Myth -- Chapter One: Literacy, Religion, and Textbooks -- Chapter Two: The Religious Nature of Early Women's Literacy -- Chapter Three: U.S.-Based Convents and the Literacy Experience -- Chapter Four: Literacy in Convent Schools of European-Based Congregations -- Chapter Five: Literacy, Benevolence, and the Paradox of Good Works -- Conclusion -- Appendix A -- Appendix B -- Appendix C -- Works Cited.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed August 2, 2016).
Master record variable field(s) change: 050
Keywords: Catholic Church -- Education -- United States -- History -- 19th century; Women -- Education -- United States -- History -- 19th century; Literacy -- United States -- History -- 19th century; Women in education -- United States -- History -- 19th century; Catholic teachers -- United States -- History -- 19th century; LANGUAGE ARTS & DISCIPLINES -- Literacy; EDUCATION -- History; RELIGION -- Christianity -- Catholic; EDUCATION / Essays; EDUCATION / Organizations & Institutions; EDUCATION / Reference; History; Electronic books